1982
DOI: 10.1139/b82-199
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and release of plant nutrients in decomposing Scots pine needle litter. Long-term decomposition in a Scots pine forest II

Abstract: Plant nutrient dynamics in decomposing needle litter were measured during a 5-year period in a Scots pine forest in central Sweden. As seen over the whole 5-year period, the nutrients were retained (to a litter weight loss of about 75%) in the order Mn < Ca < K < Mg < S < N < P. During the first 1.5 years there was a net increase of N and P whereafter a net release took place. A similar but less pronounced development could be seen for S, whereas Ca, K, Mn, and Mg were released from the start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
127
2
7

Year Published

1984
1984
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 299 publications
(159 citation statements)
references
References 14 publications
23
127
2
7
Order By: Relevance
“…Our finding that the metal dynamics during litter decomposition in a lotic ecosystem are similar to previous observations on forest floors (Staaf and Berg 1982;Lomander and Johansson 2001) suggests that a general pattern may exist for the fate of metallic elements in decomposing litter in both terrestrial and aquatic ecosystems. However, litter mass loss was much higher in the river compared with the results observed in our previous study on the forest floor for a comparable period, and metallic elements in decomposing river litter showed some unique release patterns that could be affected by multiple factors.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Our finding that the metal dynamics during litter decomposition in a lotic ecosystem are similar to previous observations on forest floors (Staaf and Berg 1982;Lomander and Johansson 2001) suggests that a general pattern may exist for the fate of metallic elements in decomposing litter in both terrestrial and aquatic ecosystems. However, litter mass loss was much higher in the river compared with the results observed in our previous study on the forest floor for a comparable period, and metallic elements in decomposing river litter showed some unique release patterns that could be affected by multiple factors.…”
Section: Discussionsupporting
confidence: 88%
“…With constant moisture, temperature in lotic ecosystems is likely to be one of the primary factors controlling microbial and decomposer activities (Martínez et al 2014), thereby modulating the litter decomposition process and the simultaneous process of element release. The dynamics of metallic elements are related to chemical characteristics, such as solubility and mobility (Staaf and Berg 1982), and thus, metallic elements with higher mobility (e.g., Ca and Na) may be less influenced by water flow velocity. Similarly, because pH typically influences the solubility and mobility of metallic elements during litter decomposition, changes in pH may have little influence on Na or Fe but can significantly influence some other metallic elements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The spatiotemporal variability of litterfall strongly depends on forest stand species (Binkley 1996) and nutritional condition during the growing season (Diaz-Maroto and Vila-Lameiro 2005). A previous study has confirmed that the nutrient of twigs and leaves can be from soil via roots and from the atmosphere through stomata (Staaf and Berg 1981). For different forest stand species, seasonal fluctuations of N concentrations in green litterfall, with the maximum values in fresh leaves and the minimum values in old ones, have been reported in the literatures (Martínez-Alonso et al 2007;Hansen et al 2009;Fife et al 2008).…”
Section: Introductionmentioning
confidence: 61%